Records of Naididae and Lumbriculidae (Clitellata) from Tibet, China, with description of a new species of Nais - Cui, Yongde; He, Xuebao; Peng, Yu; Wang, Hongzhu (Zootaxa, 2015)
The Tibetan Plateau is considered to have a unique fauna of fish and invertebrates. However, little taxonomic work has been conducted on the aquatic Oligochaeta of Tibet, China. Based on the surveys of rivers and lakes in this region between 2010 and 2011, we recorded 25 species of oligochaetes belonging to 2 families and 15 genera. This paper provides an overview of the species composition of different waterbodies, the description of one new species, Nais longidentata sp. n., and re-descriptions of four previously described species. Hitherto, 30 species of aquatic oligochaetes have been recorded from Tibet. The oligochaete fauna is similar to that of the Holarctic, but has several endemic elements.